1983
DOI: 10.1177/019459988309100108
|View full text |Cite
|
Sign up to set email alerts
|

A study of the high‐risk registry for sensorineural hearing impairment

Abstract: In the medical evaluation, rehabilitation, and education of the hearing impaired, the first line of defense is the high-risk factor screening for sensorineural damage of all neonates. The most efficacious means of neonatal screening for those factors affecting sensorineural hearing damage is the employment of a high-risk registry. Based on a retrospective study of 109 children with sensorineural loss, high-risk factors and how improved use of the high-risk registry permits earlier detection (and statistically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 7 publications
1
23
0
Order By: Relevance
“…Downs and Sterritt [1964] and Downs and Hemenway [1969] expanded these early nursery-based investigations to evaluate methodology and results of behavioral hearing screening in neonates. Based on behavioral screening of more than 17,000 newborns, Downs and Hemenway reported that 1) their behavioral technique permitted identification of infants with severe-to-profound hearing loss but failed to detect infants with milder forms of hearing impairment, 2) approximately one in 1,000 infants were born deaf, and 3) one-half of the identified infants exhibited risk factors for hearing loss, a finding remarkably similar to later reports [Pappas, 1983;Elssman et al, 1987;Mauk et al, 1991].…”
Section: Historical Contextsupporting
confidence: 61%
See 1 more Smart Citation
“…Downs and Sterritt [1964] and Downs and Hemenway [1969] expanded these early nursery-based investigations to evaluate methodology and results of behavioral hearing screening in neonates. Based on behavioral screening of more than 17,000 newborns, Downs and Hemenway reported that 1) their behavioral technique permitted identification of infants with severe-to-profound hearing loss but failed to detect infants with milder forms of hearing impairment, 2) approximately one in 1,000 infants were born deaf, and 3) one-half of the identified infants exhibited risk factors for hearing loss, a finding remarkably similar to later reports [Pappas, 1983;Elssman et al, 1987;Mauk et al, 1991].…”
Section: Historical Contextsupporting
confidence: 61%
“…Based on this approach, an infant's hearing is screened only if s/he is identified "atrisk" on the basis of defined criteria such as bacterial meningitis, in utero infection, craniofacial anomaly, or other factors. [Pappas, 1983;Elssman et al, 1987;Mauk et al, 1991]. Second, despite wellknown recommendations for screening infants at-risk and decades of advocacy for early identification, the average age of identification for children with hearing loss in the United States stalled at about 12 to 18 months [Stein et al, 1983;Elssman et al, 1987;Stein et al, 1990;Harrison and Roush, 1996].…”
Section: Historical Contextmentioning
confidence: 99%
“…What is more some studies have reported additional risk factors associated with hearing loss such as admission to intensive care unit, premature birth, respiratory distress syndrome and intracranial hemorrhage [9][10][11][12][13]. It was proven that the screening protocol based on the JCIH risk factors identifies only 50-75% of infants with hearing loss [14][15][16]. Therefore, it is now recommended to conduct universal hearing screening in all infants before third month of life.…”
Section: Introductionmentioning
confidence: 99%
“…This delay has been associated with adverse effects on speech and language development, academic achievement, and social-emotional development (4). Newborn hearing screening on the basis of risk factors alone is only able to identify approximately 50% of infants with significant hearing loss (5,6). Partially in response to the inefficiency of risk factor based screening, interest in establishing programs of universal newborn hearing screening (UNHS) began to build throughout the 1990s (7Y9).…”
mentioning
confidence: 99%